The Analysis of Public Service Management in Kota Serang. The Study of the online Application “RABEG” (Reaksi atas Berita Warga) - Indra Nizar; Budi Hasanah; Annisarizki Annisarizki; Budi Mulyati (Future Science, 2023)
The application of RABEG, is one of the media used to improve the services for people in Kota Serang. Howerver, its implementation has many problems, as reflected in the responses and assessments from users on the playstore platform, regarding the Rabeg application. The assessment given to this application was low, only 1.6 on a scale of 5. This research aimed to analyse the public service management in Kota Serang, focusing on the online Rabeg application. The research used descriptive qualitative approach, referred to the theoretical framework from Indrajit. It identified six important indicators; content development, competency building, connectivity, cyber law, citizen interface and capital. The data source were literature from books, mass media, official government documents, official website, the play store platform, and related journals. The findings of the research showed that the management of public services of Rabeg application was face with several obstacles and shortcomings. So the optimizing of public services from this application had not fully achieved.